2010
DOI: 10.1002/mrm.22399
|View full text |Cite
|
Sign up to set email alerts
|

Noncompartmental kinetic analysis of DCE‐MRI data from malignant tumors: Application to glioblastoma treated with bevacizumab

Abstract: (2)) or the IAUCBA (3) (initial area under the Gd concentration time curve in tumor, blood adjusted) in one or more malignant target lesions upon drug treatment have been recommended as primary measures of drug activity (4). The DCE-MRI results from each lesion are usually summarized by one number, the percentage change of K trans or IAUCBA from baseline upon drug treatment. The DCE-MRI parameters are estimated from the contrast agent (CA) concentration time course in the entire tumor, in a selected tumor subv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Therefore, the decision to continue with bevacizumab, or not, can be made as early as 3 days after administration of bevacizumab monotherapy, with minimal cost or side effects. This result was consistent with the results of previous studies reporting that K trans can be used as a prognostic biomarker that reflects microvascular change after antiangiogenic therapy, even when the target tumors, the drugs used, or the day that DCEMRI results are obtained (usually 14 days after treatment) are different [9,11,12,19-21]. Our study results support the hypothesis that DCE-MRI can be used as a prognostic biomarker for the bevacizumab therapy used for CRCLM treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the decision to continue with bevacizumab, or not, can be made as early as 3 days after administration of bevacizumab monotherapy, with minimal cost or side effects. This result was consistent with the results of previous studies reporting that K trans can be used as a prognostic biomarker that reflects microvascular change after antiangiogenic therapy, even when the target tumors, the drugs used, or the day that DCEMRI results are obtained (usually 14 days after treatment) are different [9,11,12,19-21]. Our study results support the hypothesis that DCE-MRI can be used as a prognostic biomarker for the bevacizumab therapy used for CRCLM treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Harrer et al [33] used the TK and ETK models to estimate permeability on 18 high-grade gliomas, and they found that K trans⁡ values calculated by using the TK model were considerably higher than the K trans⁡ values obtained using the ETK technique. On the other hand, Port et al [34] estimated the difference between noncompartmental, TK and ETK models on 20 patients with recurrent glioblastoma, finding significant differences in the results obtained with the different models.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF therapies including bevacizumab have been shown to rapidly decrease vascular permeability which manifests as a decrease in contrast enhancement (4,5). Clinical trials of bevacizumab have shown impressive radiographic response rates leading to prolongation of progression-free survival but the impact of this therapy on overall survival is not known (6,7).…”
Section: Introductionmentioning
confidence: 99%